Identification of glycogen synthase kinase 3α as a therapeutic target in melanoma. (19th September 2013) - Madhunapantula, SubbaRao V.; Sharma, Arati; Gowda, Raghavendra; Robertson, Gavin P.
Summary: Deregulated expression or activity of kinases can lead to melanomas, but often the particular kinase isoform causing the effect is not well established, making identification and validation of different isoforms regulating disease development especially important. To accomplish this objective, an siRNA screen was undertaken that which identified glycogen synthase kinase 3α (GSK3α) as an important melanoma growth regulator. Melanocytes and melanoma cell lines representing various stages of melanoma tumor progression expressed both GSK3α and GSK3β, but analysis of tumors in patients with melanoma showed elevated expression of GSK3α in 72% of samples, which was not observed for GSK3β. Furthermore, 80% of tumors in patients with melanoma expressed elevated levels of catalytically active phosphorylated GSK3α (pGSK3αY279), but not phosphorylated GSK3β (pGSK3βY216). siRNA‐mediated reduction in GSK3α protein levels reduced melanoma cell survival and proliferation, sensitized cells to apoptosis‐inducing agents and decreased xenografted tumor development by up to 56%. Mechanistically, inhibiting GSK3α expression using siRNA or the pharmacological agent AR‐A014418 arrested melanoma cells in the G0/G1 phase of the cell cycle and induced apoptotic death to retard tumorigenesis. Therefore, GSK3α is a key therapeutic target in melanoma.